The solution of the Ornstein - Zernike relation in the HNC approximation for a dusty plasma with finite size particles - Davletov, A. E.; Yerimbetova, L. T.; Mukhametkarimov, E. S. (Recent Contributions to Physics, 2013)
We study the equilibrium properties of a dusty plasma with finite-size particles by solving the Ornstein-Zernike relation in the hyper-netted chain approximation. The behavior of the radial distribution function is investigated in a wide range of plasma parameters and it is demonstrated that the formation of short- or even long-range order in the system turns possible. Polarization effects are taken into account in the interactionof finite size dust particles which provides an additional mechanismof attraction between the dust grains. For sake of simplicity, the particles are considered to be solid metal balls whose interaction is strongly influenced bythe phenomenon of electrostatic induction and treated by the image method.